Do glycemic marker levels vary by race? Differing results from a cross-sectional analysis of individuals with and without diagnosed diabetes. Issue 1 (10th June 2016) - Carson, April P; Muntner, Paul; Selvin, Elizabeth; Carnethon, Mercedes R; Li, Xuelin; Gross, Myron D; Garvey, W Timothy; Lewis, Cora E
Abstract : Objective: It is well known that A1c varies by race. However, racial differences in other biomarkers of hyperglycemia are less well characterized. The objective of this study was to determine whether average levels of glycemic markers differ by race in adults with and without diagnosed diabetes, before and after accounting for postchallenge glucose. Research design and methods: This cross-sectional study included 2692 middle-aged men and women (5.5% with diagnosed diabetes; 44% African-American; and 56% white) from the Coronary Artery Risk Development in Young Adults Study (2005–2006) who had fasting glucose, 2-hour postchallenge glucose, A1c, glycated albumin, fructosamine, and 1, 5-anhydroglucitol (1, 5-AG) measured. Multiple linear regression was used to evaluate racial differences in mean levels of each glycemic marker stratified by the diabetes status and adjusted for sociodemographics, cardiovascular factors, and postchallenge glucose. Results: Among those with diagnosed diabetes, racial differences were not observed for any of the glycemic markers. In contrast, among those without diagnosed diabetes, African-Americans had higher mean levels than whites of A1c (β=0.19% points; 95% CI 0.14 to 0.24), glycated albumin (β=0.82% points; 95% CI 0.68 to 0.97), fructosamine (β=8.68 μmol/L; 95% CI 6.68 to 10.68), and 2-hour glucose (β=3.50 mg/dL; 95% CI 0.10 to 6.90) after multivariable adjustment, whereas there were no statistically significant racial difference in 1, 5-AG. The racial differences observed for A1c, glycated albumin, and fructosamine persisted after further adjustment for fasting and 2-hour glucose and were of similar magnitude (SD units). Conclusions: Racial differences in glycemic marker levels were evident among middle-aged adults without diagnosed diabetes even after adjustment for postchallenge glucose. Whether these racial differences in biomarkers of hyperglycemia affect the risk of complications warrants additional study.